Recent applications of Kirkwood–Buff theory to biological systems - Pierce, Veronica; Kang, Myungshim; Aburi, Mahalaxmi; Weerasinghe, Samantha; Smith, Paul E. (My University, 2011)
The effect of cosolvents on biomolecular equilibria has traditionally been rationalized using simple binding models. More recently, a renewed interest in the use of Kirkwood–Buff (KB) theory to analyze solution mixtures has provided new information on the effects of osmolytes and denaturants and their interactions with biomolecules. Here we review the status of KB theory as applied to biological systems. In particular, the existing models of denaturation are analyzed in terms of KB theory, and the use of KB theory to interpret computer simulation data for these systems is discussed.
Keywords: Preferential binding; Preferential interactions; Kirkwood-Buff theory; Protein denaturation; Cosolvents; Osmolytes; Computer simulation